A presença da cultura de matrizes africanas baseada na lei 10.639/2003 em livros didáticos de matemática - RODRIGUES, Mony Tarler Maciel (2023)
This work deals with a survey of the laws that guide and standardize the dissemination of knowledge of Afro-Brazilian culture, which are present in textbooks. Our objective is to identify the elements that can be worked on in mathematics classes, having as parameters the African matrix culture. The methodology of this study is the bibliographic and documentary survey, based on the laws that govern Brazilian education regarding the production of textbooks. As a result, we hope to understand the motivations and obstacles to the use of African cultures in textbooks.